Revolutionizing Electric Vehicle Sustainability: IoT-Enabled Monitoring of Lithium-Ion Batteries for Enhanced Performance and Safety: DOI: 10.56815/IJEMS.V3.I1.2023/20-30 (International Journal of Engineering Management Science, 2023)
The rise of Electric Vehicles (EVs) as a sustainable mode of transportation hinges on the efficacy of Lithium-Ion (Li-ion) batteries.This paper explores the transformative impact of Internet of Things (IoT) technology in advancing EV sustainability through real-timemonitoring of Li-ion batteries. As EV adoption grows, ensuring the optimal performance and longevity of Li-ion batteries becomesparamount. The integration of IoT offers a solution by enabling continuous monitoring through sensors, communication protocols, and cloud-based platforms. Critical parameters such as voltage, temperature, state of charge (SoC), state of health (SoH), current, andinternal resistance are identified for comprehensive battery health management. The paper investigates advancements such as predictive maintenance and anomaly detection, leveraging real-time data to proactively address potential issues. Case studies from diverse manufacturers and regions illustrate successful implementations and challenges faced in IoT-enabled Li-ion battery monitoring. Acknowledging challenges like security concerns, the paper outlines strategies to overcome them and envisions future prospects, including the integration of artificial intelligence for more sophisticated battery health prediction. In conclusion, IoT integration revolutionizes EV sustainability by ensuring enhanced performance and safety, solidifying the foundation for widespread acceptance of electric mobility.
Keywords: Electric Vehicles, LithiumIon Batteries, IoT, Battery Monitoring, Sustainability, Performance Optimization, Safety Enhancement